2016
DOI: 10.1002/bjs.10178
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing self-gripping mesh with a standard polypropylene mesh for open inguinal hernia repair

Abstract: NTR1212 (http://www.trialregister.nl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 21 publications
(34 reference statements)
3
32
0
Order By: Relevance
“…The operative duration is significantly shorter in this study and similar conclusion drawn by Zhang et al and Fang et al 9,10 Significant reduction of early postoperative pain which helped the patient for early return to day to day activities in this study is also comparable to the earlier studies. 7,11,12 Another study Fan et al, there is no recurrence with comparison to present study in P group. 13 …”
Section: Discussionsupporting
confidence: 46%
“…The operative duration is significantly shorter in this study and similar conclusion drawn by Zhang et al and Fang et al 9,10 Significant reduction of early postoperative pain which helped the patient for early return to day to day activities in this study is also comparable to the earlier studies. 7,11,12 Another study Fan et al, there is no recurrence with comparison to present study in P group. 13 …”
Section: Discussionsupporting
confidence: 46%
“…Of 2682 articles identified by the literature search, 51 were selected for full‐text assessment and 29 articles met the inclusion criteria. After removing duplicate articles, 25 were included in the meta‐analysis, representing 23 studies ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…One study had a multiarm trial design comparing cyanoacrylate glue fixation and ProGrip™ self‐gripping mesh with suture fixation of the mesh. Five studies reported on fibrin glue fixation, eight on cyanoacrylate glue fixation and 11 on the use of ProGrip™ self‐gripping mesh. Of the 23 articles included in the meta‐analysis, 15 provided the incidence of chronic pain at 12 months, according to the definition provided in the methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the aforementioned recommendation that there is still a need to fixate mesh prostheses in some instances, namely a large direct hernia (M3 and above) (8), it is likely that it will take some time and considerable evidence for no-fixation to be widely adopted in practice. With the possibility that self-gripping mesh technology may play a role in advancing this movement (28). …”
Section: Discussionmentioning
confidence: 99%